The Assertive Communication Style of English Language Education Students in Verbal Interaction: A Descriptive Study - Abdul Malik Badrudin; Wendi Kusriandi; Agus Wirabhakti (Journal of English Language and Education, 2026)
Assertive communication is a communication style that enables individuals to express thoughts, feelings, and opinions openly, honestly, and confidently while respecting the rights of others. This study aims to describe how students of the English Language Education Study Program apply assertive communication in their everyday verbal and non-verbal interactions. A qualitative descriptive approach was employed. Data were collected through classroom observations and semi-structured interviews with four students. The research instrument was developed based on the assertive communication indicators proposed by Samfira (2020) and Yoshinaga and Cooper (2025), complemented by recent studies on assertive communication in language education (Ogunyemi Olagbaju, 2020; Hastuti Wijayanto, 2023). The verbal findings revealed that all participants consistently demonstrated openness, the use of “I” statements, respect for their own rights and those of others, non-aggressive firmness, and contextual appropriateness through empathic assertion. In contrast, the non-verbal findings showed greater variation, particularly in maintaining eye contact, with three participants displaying limited eye contact and one participant demonstrating it consistently. Triangulation of observation and interview data also identified discrepancies between self-perceived and actual communication behaviors, as well as individual differences in empathic assertion strategies. These findings contribute to understanding assertive communication development among prospective English teachers.